Future Trends in Pharmaceuticals: Investigation of the Role of AI in Drug Discovery, 3D Printing of Medications, and Nanomedicine: Artificial Intelligence in Nanomedicine - Paneru, Biplov; Paneru, Bishwash (Universitas Komputer Indonesia, 2023)
The pharmaceutical sector has to deal with issues like high costs, difficult diseases, and the demand for tailored therapy. The transformational potential of AI, 3D printing, and nanomedicine is examined in this paper. Drug development is revolutionized by AI, which also predicts effectiveness and personalizes therapies. Tailors, prescriptions, and complex documents can all be 3D printed to help with compliance. Nanoparticles are used in nanomedicine to deliver drugs more precisely and enhance solubility. Future themes include AI-driven target identification and individualized treatment; the effectiveness and role of 3D printing in personalized medicine; and improved medication delivery through nanomedicine. These developments promise to alter healthcare, which will help a lot of people. The study results offers a thorough examination of upcoming trends in the pharmaceutical industry and similarly discusses developments in 3D printing and nanomedicine.